DNA probe- and PCR-based methods for the detection of trypanosomes - Majiwa, Phelix A.O. (OAU/STRC, 1995)
Accurate identification of an infectious organism facilitates the study of epidemiology of the disease it causes and makes possible rational evaluation of the relative success of different control strategies. Highly repetitive, tandem or interspersed DNA sequences unique to different species, type or sub-type of the African trypanosomes have been cloned as recombinant plasmids for use in specific and sensitive identification of the trypanosomes. Protocols have been adapted for use with these DNA probes in the detection of trypanosomes in the blood or buffy coat samples from mammalian hosts and the saliva of live tsetse flies. The detection of parasite DNA relies upon hybridization with parasite type-specific DNA probe labelled with digoxigenin, followed by revealing the hybridized probe using anti-digoxigenin antibodies conjugated to alkaline phosphatase and the addition of enzyme substrates resulting in either visible colour or emission of light detectable by autoradiography. Combined with the polymerase chain reaction (PCR), the method detects trypanosomes in bufffy-coat samples from antigenaemic but aparasitaemic cattle, and in the saliva of live infected tsetse flies. The majority of these recombinant DNA probes are presently available from various sources.